2020
DOI: 10.23822/eurannaci.1764-1489.157
|View full text |Cite
|
Sign up to set email alerts
|

IgG from atopic individuals can mediate non atopic infant thymic and adult peripheral CD8 TC2 skewing without influence on TC17 or TC22 cells

Abstract: The potential of IgG antibodies as allergy regulators has been discussed for decades and was brought to light that anti-allergen IgG is related to allergy inhibition in children during the first years of life and that IgG repertoire can differ between atopic and non-atopic individuals. Here, we aimed to evaluate in vitro the differential effects of purified IgG from atopic and non-atopic individuals on the production of IL-4, IL-17, and IL-22 by human intra-thymic and mature peripheral CD8 + T cells respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Some in vitro studies have also demonstrated that atopic IgG repertoire can modulate CD8+ T cell functions. Recently, it was shown that IgG from atopic individuals could induce non-atopic infant thymic and adult peripheral CD8+ T cells to produce IL-4, acquiring a TC2 profile [ 30 ]. However, this study did not investigate if this effect was mediated by the direct interaction of IgG with CD8+ T cell membrane, not even TCRs.…”
Section: Experimental Evidence On the Immune Tolerance Induced By Iggmentioning
confidence: 99%
“…Some in vitro studies have also demonstrated that atopic IgG repertoire can modulate CD8+ T cell functions. Recently, it was shown that IgG from atopic individuals could induce non-atopic infant thymic and adult peripheral CD8+ T cells to produce IL-4, acquiring a TC2 profile [ 30 ]. However, this study did not investigate if this effect was mediated by the direct interaction of IgG with CD8+ T cell membrane, not even TCRs.…”
Section: Experimental Evidence On the Immune Tolerance Induced By Iggmentioning
confidence: 99%
“…In the last 24 h, 10 µg/mL Brefeldin A (Sigma, Israel) was added only to the wells dedicated to evaluating intracellular cytokine production. This protocol was previously standardized using positive (Phorbol 12-myristate 13-acetate-PMA) and negative controls (mock condition), and due to the absence of polyclonal stimulation, we could maintain Brefeldin A for 24 h without decreasing cell viability (32,34,35,37,38,42).…”
Section: Freezing and Thawing Of Thymic Cells Suspensionmentioning
confidence: 99%
“…Previous studies in the literature demonstrated that IgG antibodies could interact with lymphocytes precursors in the murine and human thymus, modulating its cytokine production as recently revised ( 31 ). Together, these pieces of evidence suggest that atopic and non-atopic individuals' IgG repertoire can differentially modulate the maturation of thymic TCD4, TCD8, iNKT B, and γδT cells modulating or inhibiting the development of allergy ( 32 42 ). In those observations, it has become evident that IgG antibodies can interact with a wide range of clonal or conserved receptors expressed in several cell populations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the "hooks without bait" immunological hypothesis proposed that polyclonal IgG repertoires from different donor groups may play essential roles in modulating the function of thymic and peripheral T and B cells 16 . In this context, polyclonal IgG from individuals with allergies, atopic dermatitis, HIV infection, and HTLV infection has demonstrated in vitro modulatory effects on various thymic and peripheral lymphocytes, including T cells, B cells, γδT cells, iNKT cells, and innate-like cells (ILC) in both humans and mice 17 25 . These effects have the potential to modulate the pathophysiology of these diseases.…”
Section: Introductionmentioning
confidence: 99%